(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The purpose of the study was to assess the practices of leadership styles that influence employees’ job performance. In the case of the Bole sub-city education sector, Addis Ababa, Ethiopia. The results of the research were mixed. Some are positive results and some are negative results. For a long time, most research scholars and academicians have taken various leadership styles that are conducted under different leadership theories. This study has selected leadership styles such as transformational, transactional, Autocratic and servant leadership styles as independent variables that are supposed to have a direct effect on employees’ job performance which is the dependent variable. A questionnaire was developed using different past literature which is similar to this title on the study of leadership style and employees performance. A sample of 110 respondents was recruited using simple random probability sampling techniques. Collected data for this research was recorded and analysed using SPSS 20.0. the result of the research shows that transformational and servant leadership behaviours positively and significantly influence employees’ performance at the workplace. And the remaining Autocratic and transactional leadership behaviours are not significant in influencing employees’ performance. Depending on the finding researchers concluded that transformational and servant leadership behaviours directly influence employee performance. Managers or leaders and also team leaders in any governmental or private organization should find ways to use especially servant leadership behaviour to improve employee job performance, especially among department heads, district level education heads; district level education heads and officers in the sub-city.